2015
DOI: 10.1186/s12885-015-1935-0
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage traits in cancer cells are induced by macrophage-cancer cell fusion and cannot be explained by cellular interaction

Abstract: BackgroundCell fusion is a natural process in normal development and tissue regeneration. Fusion between cancer cells and macrophages generates metastatic hybrids with genetic and phenotypic characteristics from both maternal cells. However, there are no clinical markers for detecting cell fusion in clinical context. Macrophage-specific antigen CD163 expression in tumor cells is reported in breast and colorectal cancers and proposed being caused by macrophages-cancer cell fusion in tumor stroma. The purpose of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
81
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(88 citation statements)
references
References 31 publications
5
81
0
2
Order By: Relevance
“…This phenomenon is a more efficient mechanism of DNA-exchange and cellular reprogramming than the accumulation of mutations in single cells (Bastida-Ruiz et al 2016; Dittmar et al 2013; Duelli and Lazebnik 2003). Growing in vitro (Busund et al 2002, 2003; Shabo et al 2015; Wei et al 2014), in vivo (Powell et al 2011; Silk et al 2013), and clinical (LaBerge et al 2017; Lazova et al 2013; Yilmaz et al 2005) data indicate that this process occurs in solid tumors and may play a significant role in clinical tumor progression. Moreover, this process generates malignant cell clones (hybrids) with reduced susceptibility to oncological treatments (Carloni et al 2013; Nagler et al 2011; Wang et al 2012; Yang et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon is a more efficient mechanism of DNA-exchange and cellular reprogramming than the accumulation of mutations in single cells (Bastida-Ruiz et al 2016; Dittmar et al 2013; Duelli and Lazebnik 2003). Growing in vitro (Busund et al 2002, 2003; Shabo et al 2015; Wei et al 2014), in vivo (Powell et al 2011; Silk et al 2013), and clinical (LaBerge et al 2017; Lazova et al 2013; Yilmaz et al 2005) data indicate that this process occurs in solid tumors and may play a significant role in clinical tumor progression. Moreover, this process generates malignant cell clones (hybrids) with reduced susceptibility to oncological treatments (Carloni et al 2013; Nagler et al 2011; Wang et al 2012; Yang et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, we showed that macrophage:MCF-7 hybrids can be generated spontaneously at an average rate of 2% (Shabo et al 2015). One gram of tumor mass is assumed to contain approximately 1 × 10 8 tumor cells (Del Monte 2009), suggesting theoretically that each gram of breast cancer tissue may potentially generate approximately 2 million hybrid cells.…”
Section: Discussionmentioning
confidence: 99%
“…The myeloid mimicry phenomenon in cancer cells has been reported previously in several cancer entities, including breast cancer, colorectal cancer and pancreatic cancer, and it is associated with advanced disease and worse outcomes (21)(22)(23). Some studies determined that the expression of myeloid markers by cancer cells was a result of cancer cell-immune cell fusion, and thus created hybrids that express characteristics of both cellular origins (24)(25)(26). In our study, we determined that FACS-sorted malignant epithelial cells and murine KPC cell lines express chemokine (C-C motif) ligand 9 (CCL9), arginase 1 (ARG1), and cluster of differentiation 68 (CD68), but do not express CD45, the transmembrane protein expressed by all hematopoietic cells, suggesting that the myeloid mimicry phenomenon we reported here is not a consequence of cell fusion.…”
Section: Discussionmentioning
confidence: 91%
“…Cell fusion is a natural biological process in normal development and tissue regeneration (207,208). Fusion between cancer cells and macrophages results in hybrids that acquire genetic and phenotypic characteristics from both maternal cells (129,139,209). There is a growing body of in vitro and in vivo data indicating that this process also occurs in solid tumors and may play a significant role in tumor progression (133,134,138,139,210,211).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the cell fusion theory, it has been suggested that macrophage phenotype in cancer cells might be caused by fusion between tumor-associated macrophages (TAM) and cancer cells (129,138,139).…”
Section: The Theory Of Cell Fusion and Macrophage Traits In Cancer Cellsmentioning
confidence: 99%